English wheel of revision game (ENL WOR-G) / Rahimah Abd Wahab ... [et al.] - Abd Wahab, Rahimah; Hussin, Adibah; Abdul Razak, Nor Hidayatun; Ishak, Maisarah (2022)
Learning English is often perceived as a tedious process that involves remembering a lot of rules. The ENL WOR-G game is specially designed to add fun and excitement to the learning process. Students who have tried this game felt very enthusiastic about it and all of them would recommend the game to their language instructors. All agreed that this game could help them improve their language. This game can be easily adaptable to different age groups and levels of proficiency. Thus, the innovative use of the ENL WOR-G game suggested here can be utilized by language instructors in and outside the classroom to enable students to remember aspects of the English language in a fun and entertaining way.